AAV-mediated gene therapy: Advancing cardiovascular disease treatment - Zhang, Huili; Zhan, Qi; Huang, Biao; Wang, Yigang; Wang, Xiaoyan (Frontiers in Cardiovascular Medicine, 2022)
Gene therapy has revolutionized the field of medicine, offering new hope for those with common and rare diseases. For nearly three decades, adeno-associated virus (AAV) has shown significant therapeutic benefits in multiple clinical trials, mainly due to its unique replication defects and non-pathogenicity in humans. In the field of cardiovascular disease (CVD), compared with non-viral vectors, lentiviruses, poxviruses, and adenovirus vectors, AAV possesses several advantages, including high security, low immunogenicity, sustainable and stable exogenous gene expression etc., which makes AAV one of the most promising candidates for the treatment of many genetic disorders and hereditary diseases. In this review, we evaluate the current information on the immune responses, transport pathways, and mechanisms of action associated with AAV-based CVD gene therapies and further explore potential optimization strategies to improve the efficiency of AAV transduction for the improved safety and efficiency of CVD treatment. In conclusion, AAV-mediated gene therapy has great potential for development in the cardiovascular system.